System optimization of parameters of diamond grinding - Yenikieiev, A. F.; Yevsiukova, F. M.; Zykov, I. S.; Prihodko, O. Y.; Abramska, I. B. (Global Science Center LP, 2017)
It is offered the indirect methods for measuring of the roughness of the machined surface of the workpiece and cutting characteristics of the grinding wheel. It is built a three-level multiprocessor system for optimizing the parameters of the diamond grinding process based on these indirect methods as well as the method of coordinate-wise control and the principle of deviation control. It is developed mathematical models of hardware of the system taking into account the uncertainty factors which are caused by interference and inaccuracies in the measurement of input signals. It is built the schemes of computer modeling of processes of transformation of input information by hardware.
Keywords: multiprocessor system; hardware; indirect measurements; computer simulation